The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/desc.12480
|View full text |Cite
|
Sign up to set email alerts
|

Tracing trajectories of audio‐visual learning in the infant brain

Abstract: Although infants begin learning about their environment before they are born, little is known about how the infant brain changes during learning. Here, we take the initial steps in documenting how the neural responses in the brain change as infants learn to associate audio and visual stimuli. Using functional near-infrared spectroscopy (fNRIS) to record hemodynamic responses in the infant cortex (temporal, occipital, and frontal cortex), we find that across the infant brain, learning is characterized by an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 30 publications
(53 reference statements)
7
38
1
Order By: Relevance
“…For example, functional near-infrared spectroscopy (fNIRS) has been used to investigate learning trajectories (Kersey & Emberson, 2017) and responses to novelty or violations (Emberson, Richards, & Aslin, 2015;Lloyd-Fox et al, 2019;Nakano, Watanabe, Homae, & Taga, 2009 Orena & Polka, 2017). For example, functional near-infrared spectroscopy (fNIRS) has been used to investigate learning trajectories (Kersey & Emberson, 2017) and responses to novelty or violations (Emberson, Richards, & Aslin, 2015;Lloyd-Fox et al, 2019;Nakano, Watanabe, Homae, & Taga, 2009 Orena & Polka, 2017).…”
Section: Perceptual Modalitymentioning
confidence: 99%
“…For example, functional near-infrared spectroscopy (fNIRS) has been used to investigate learning trajectories (Kersey & Emberson, 2017) and responses to novelty or violations (Emberson, Richards, & Aslin, 2015;Lloyd-Fox et al, 2019;Nakano, Watanabe, Homae, & Taga, 2009 Orena & Polka, 2017). For example, functional near-infrared spectroscopy (fNIRS) has been used to investigate learning trajectories (Kersey & Emberson, 2017) and responses to novelty or violations (Emberson, Richards, & Aslin, 2015;Lloyd-Fox et al, 2019;Nakano, Watanabe, Homae, & Taga, 2009 Orena & Polka, 2017).…”
Section: Perceptual Modalitymentioning
confidence: 99%
“…We are looking to uncover the same inverted u‐shaped neural changes that were observed in Kersey and Emberson () for this type of learning and contrast these trajectories across the two populations of infants. In addition to contrasting trajectories, we conduct an individual differences analysis (as in Kersey & Emberson, ) to investigate how variations in an infant's ability to generate top‐down prediction relates to their individual learning trajectories. We expect to find a positive correspondence between the emergence of top‐down predictions and the strength of U‐shape neural trajectories during learning.…”
Section: Introductionmentioning
confidence: 73%
“…There is already some evidence that the emergency of top‐down predictions are playing some role in neural learning trajectories. Kersey and Emberson () found that full‐term infants exhibit an inverted u‐shaped learning trajectory (i.e., repetition enhancement followed by repetition suppression) during the audiovisual learning that supports the generation of top‐down predictions. In exploratory analyses, Kersey and Emberson () found that the shape of an individual infant's learning trajectory can predict an infant's individual top‐down prediction abilities (i.e., their occipital lobe response during an unexpected visual omission).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations